Impact of fever thresholds in detection of COVID‐19 in Department of Veterans Affairs Community Living Center residents. Issue 11 (4th September 2021) - Bej, Taissa; Kothadia, Sonya; Wilson, Brigid M.; Song, Sunah; Briggs, Janet M.; Banks, Richard E.; Donskey, Curtis J.; Perez, Federico; Jump, Robin L. P.
Abstract: Background: Among nursing home residents, for whom age and frailty can blunt febrile responses to illness, the temperature used to define fever can influence the clinical recognition of COVID‐19 symptoms. To assess the potential for differences in the definition of fever to characterize nursing home residents with COVID‐19 infections as symptomatic, pre‐symptomatic, or asymptomatic, we conducted a retrospective study on a national cohort of Department of Veterans Affairs (VA) Community Living Center (CLC) residents tested for SARS‐CoV‐2. Methods: Residents with positive SARS‐CoV‐2 tests were classified as asymptomatic if they did not experience any symptoms, and as symptomatic or pre‐symptomatic if the experienced a fever (>100.4°F) before or following a positive SARS‐CoV‐2 test, respectively. All‐cause 30‐day mortality was assessed as was the influence of a lower temperature threshold (>99.0°F) on classification of residents with positive SARS‐CoV‐2 tests. Results: From March 2020 through November 2020, VA CLCs tested 11, 908 residents for SARS‐CoV‐2 using RT‐PCR, with a positivity of rate of 13% (1557). Among residents with positive tests and using >100.4°F, 321 (21%) were symptomatic, 425 (27%) were pre‐symptomatic, and 811 (52%) were asymptomatic. All‐cause 30‐day mortality among residents with symptomatic and pre‐symptomatic COVID‐19 infections was 24% and 26%, respectively, while those with an asymptomatic infection had mortality rates similar to residents with negative SAR‐CoV‐2 tests (10% and 5%, respectively). Using >99.0°F would have increased the number of residents categorized as symptomatic at the time of testing from 321 to 773. Conclusions: All‐cause 30‐day mortality was similar among VA CLC residents with symptomatic or pre‐symptomatic COVID‐19 infection, and lower than rates reported in non‐VA nursing homes. A lower temperature threshold would increase the number of residents recognized as having symptomatic infection, potentially leading to earlier detection and more rapid implementation of therapeutic interventions and infection prevention and control measures.